(untitled) (Journal of International Studies, 2019)
The occurrence of criminal activities has increased owing to the advent of internet or computer technology. Access to internet has posed serious challenges to the existing legal regime and enforcement paradigm. The recent experience concerning rate of technology and online communication has no doubt fashioned-out a dramatic increase in the incidence of criminal activities. It has also resulted in the occurrence of what is considered as a new approach of criminal activities. Although, the emergence of electronic communication advances economic prosperity of the world’s commerce, fraudsters have gained access and seen the medium as a fertile ground for pretence. This paper firstly discusses the wide-ranging descriptions that led to the complex concept of cybercrime. The paper then examines the importance of cybercrimes regulations to curb infidelity in the use of computer technology. It also investigates the interface between cybercrimes and human rights and argued that human rights are an onerous matter that should be given proper consideration when dealing with cybercrime offenders. The paper utilizes legal research method by way of examining the Nigerian Cybercrimes Act 2015 and its relationship with several human rights provisions. It concludes by revealing the need to prevent cybercrimes that coincide with the right of an individual to enjoy his right to privacy and at the same time ensuring cyber security.